Serious games as research instruments – Do’s and don’ts from a cross-case-analysis in transportation - Freese, Maria; Lukosch, Heide; Wegener, Jan; König, Alexandra (European Journal of Transport and Infrastructure Research, 2020)
Serious games as research instruments are seen as a special type of participatory modelling, allowing a researcher to observe the behaviour and decisions taken by players. Yet, games have their own dynamics and come with certain challenges when used as a research instrument. This article reports on specific challenges in using games as research instruments in the domain of transportation. Therefore, three digital games from the transportation sub-systems freight transport, airport management and public transport are presented. The cases are analysed according to the challenges faced during the phases of requirements analysis, design, implementation, usage as research instrument, and evaluation. Based on this cross-case analysis of the research games, Do’s and Don’ts as well as practical recommendations are derived to support researchers and practitioners in applying serious games as research instruments in transportation. The new ReDIRE-framework to analyse serious games for research purposes is presented for this aim. Design guidelines resulting from our contribution can be helpful for game designers and researchers alike.